Older adults and violence: an analysis of Domestic Homicide Reviews in England involving adults over 60 years of age - BENBOW, SUSAN MARY; BHATTACHARYYA, SARMISHTHA; KINGSTON, PAUL (Ageing and society, 2019)
Domestic Homicide Reviews (DHRs) are conducted when an individual aged 16 or over appears to have died from violence, abuse or neglect by a person to whom they are related or with whom they are in an intimate relationship or who is a member of the same household. DHRs aim to identify lessons to be learned, to improve service responses to domestic abuse and to contribute to prevention of domestic abuse/homicide. We submitted Freedom of Information requests to English Local Authorities to identify DHRs where victim, perpetrator or both were aged over 60. Collected Reports and/or Executive Summaries were thematically analysed. Analysis identified four key themes in the context of the key relationship and caring: major mental illness of the perpetrator; drug and/or alcohol abuse; financial issues; and a history of domestic abuse in key or family relationships. We analysed 14 adult family homicides, 16 intimate partner homicides and five homicide–suicides. Age per se did not emerge as a significant factor in our analysis. Terminology needs to be standardised, and training/education regarding risk assessment needs to be improved in relation to age, myths around ageing/dementia and stresses of caring. Management of mental illness is a key factor. A central repository of DHR Reports accessible for research and subject to regular review would contribute to maximising learning and improving practice.